Time-varying parking prices - Jos Van Ommeren; Giovanni Russo (European Regional Science Association (ERSA), 2012)
According to economic theory, the price of parking must vary with the demand for this good. We study the economic consequences of not doing so by estimating the employees' parking demand at one organisation, which, rather uniquely, follows this recommendation. We estimate the effect of the employees' parking price on demand using an innovative difference-in-differences methodology. The deadweight loss generated by non-optimal pricing of parking is at least 9% of the parking resource costs.
Keywords: 330